Aswaja-Based Local Curriculum Management Strategies in Maintaining Islamic Identity in the Globalization Era (A Case Study at MA Ma'arif Pare) - Mukhamad Rifa’i; Nur Ahid; Nahid Ayad (International Journal of Religion and Social Community, 2025)
This research discusses the management strategy of Ahlussunnah wal Jama'ah (Aswaja) based local curriculum at MA Ma'arif Pare as an effort to maintain the Islamic identity of students in the era of globalization. In the face of the challenges of globalization that impact local values and Islamic culture, Islamic educational institutions must be able to respond appropriately. A qualitative approach with a case study method was used in this research to explore in depth the application of the Aswaja curriculum in both intracurricular and extracurricular learning. The results show that Aswaja values such as tawasuth (moderate), tasamuh (tolerance), tawazun (balance), and i'tidal (justice) are integrated into the learning process through routine religious activities, character strengthening, and cooperation with local religious leaders. This curriculum not only strengthens academic aspects, but also effectively instills religious and nationalistic characters in students. MA Ma'arif Pare can combine traditional Islamic values with national education policies and adapt them to the social context of the community. This demonstrates that Aswaja-based local curriculum management can serve as a strong foundation in preserving Islamic identity amidst global change.